Development and preliminary validation of socio-cultural influences on body image scale for Malaysian female adolescents - Chin, Y. S.; M. T., Mohd Nasir; Mohd Shariff, Zalilah; Khor, Geok Lin (Nutrition Society of Malaysia, 2008)
The present study aimed to develop and validate comprehensive multi-dimensional sociocultural (parental, peers, media) influence on body image scale for Malaysian female adolescents. A total of 328 female adolescents from a secondary school in Kuantan district, Pahang, Malaysiacompleted a self-administered questionnaire, which encompassed a multiple measure of sociocultural influence, Body Dissatisfaction and Body Importance subscales of Body Image Questionnaire (McCabe & Ricciardelli, 2001), and Body Change Inventory (Ricciardelli & McCabe, 2002). Through factor analysis, the three major components (parental, peers, media) of the sociocultural influence scale were found to consist of multi-dimensional constructs. Particularly, five dimensions were identified for the parental influence subscale: 1) parental teasing on weight, 2) parental encouragement on increasing muscle and weight, 3) parental social support, 4) parental preoccupation with thinness and dieting behaviour, and 5) parental feedback on body change behaviour; the peer influence subscale comprised four dimensions including 1) peer social support, 2) peer preoccupation with thinness and dieting behaviour, 3) peer teasing on weight, and 4) peer encouragement on increasing muscle and weight; and three dimensions were identified in the media influence subscale, which included 1) media encouragement on reducing weight, 2) media modeling on weight reducing behaviour, and 3) media encouragement on increasing muscle and weight. As for construct validity, there were positive correlations between the composite score of the subscales and body dissatisfaction, body importance, strategies to decrease body size and strategies to increase body size and muscle size. In short, the present study has developed a sociocultural (parental, peer, media) influences on body image scale with construct validity and good internal consistency for Malaysian female adolescents. The scale can be used to assess the various dimensions of socio-cultural influences and will be useful to determine the etiology, prevention and treatment of negative body image and its related problems for Malaysian female adolescents.